The Assessment of Science and Technology Activity in Primary Health Care: an Approach to the Subject - Zenia Tamara Sánchez García; Humberto Miguel Agüero García; Maricel Felicita Castellanos González; María Felicia Casanova; Jayce Díaz Díaz; Juan Carlos Alvarado Peruyero (Medisur)
Primary Health Care is the strategy to organize the management of health system that ensures universal access to minimum health services through equitable distribution of resources, community participation and implication of policies from other sectors. Therefore, the development of assessment in Science and Technology System at this level becomes of vital importance. The policy and management of science and technology are crucial in the strategic development of each country. In this sense, considering the convergence of the activity of science and technology with social development becomes a necessity particularly important for developing countries. The purpose of this literature review is to summarize the development of this modality in Cuba and the world, in such a way that it will serve to help people who need information on the subject.